Green Marketing in India: Some Eco-Issues - Ramakrishna, H. (Indian Journal of Marketing, 2011)
Green or Environmental Marketing satisfies human needs with minimal detrimental impact on the natural environment. Green marketing not only includes consumer goods and industrial goods, but also the services sector. In the process of distribution of goods and services, both the manufacturing and the services sector contribute towards the ecological imbalance and loss of the ozone layer. However, the role of the manufacturing sector in this regard is more significant. The process of manufacturing and selling goods and services with the least threat to the environment is a big issue before the business houses. Green marketing requires awareness not only from the consumers (consumers and industrial goods users), but also from the manufacturers of such goods. Ultimately, green marketing requires extra cost, but the stakeholders should be ready to bear that cost. Business firms have also started responding to environmental challenges by adopting and practicing green marketing strategies. The most important advantage of green marketing is that eco-friendly goods have a competitive advantage over other firms selling non-eco featured goods. At the same time, it should be noted that in the era of green marketing, each and every stakeholder should take part in this process as a social responsibility.